Method for preparing mlcc barium titanate ceramic powder from mlcc waste and multilayer ceramic capacitor
Patent Information
- Application Number
- CN202611408035.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-23
AI Technical Summary
[0005](3)火法冶炼回收:将废弃物投入有色金属冶炼炉,使镍/铜进入合金相,回收镍和铜,钛酸钡回收率低,且高温下钛酸钡中的Ti4+易被还原为Ti3+,产生氧空位,导致介电损耗增大、绝缘电阻下降
(1)本申请在去除有机杂质的低温预烧处理与重构晶相的高温煅烧处理过程之间设置掺杂工艺,完成液相化学包覆工序,使掺杂剂在颗粒尚未致密化的中间状态以分子级厚度均匀包覆于表面,再通过分段控温煅烧精确调控扩散深度。该工艺节点的选择同时克服了 “煅烧前掺杂导致钛离子还原”和“煅烧后掺杂无法形成壳层”的缺陷。
Abstract
Description
Technical Field
[0001] This application relates to the field of waste recycling technology, and in particular to a method for preparing barium titanate ceramic powder for MLCC using waste generated during MLCC production and processing, and a multilayer ceramic capacitor using the barium titanate ceramic powder. Background Technology
[0002] Multilayer ceramic capacitors (MLCCs) are the most widely used surface-mount passive components globally, extensively applied in consumer electronics, automotive electronics, and artificial intelligence servers. Barium titanate (BaTiO3) is the core matrix of MLCC dielectric materials, accounting for approximately 70% of the raw material cost of MLCCs. During MLCC production, from casting and stacking to end-face grinding, each process generates a large amount of waste, such as chamfering sludge (also known as tumbling sludge, grinding sludge, or polishing sludge). This slurry-like solid waste is formed during the chamfering / tumbling process after MLCC sintering, consisting of fine ceramic powder ground from the ceramic body, internal electrode metal fragments, abrasive particles, and water. The composition of chamfering sludge comes directly from the MLCC body, with barium titanate content typically exceeding 85%, and also containing internal electrode metals such as nickel, copper, and silver, usually at a higher percentage than the overall MLCC composition. It represents a high-value, concentrated type of electronic hazardous waste.
[0003] Currently, most MLCC manufacturing companies outsource the disposal of waste generated during MLCC production as hazardous waste, primarily through the following methods: (1) Rigid landfill: The waste is solidified and stabilized before being sent to a hazardous waste landfill and completely abandoned.
[0004] (2) Co-processing in cement kiln: Waste is fed into cement kiln for high-temperature calcination, barium titanate enters cement clinker, and nickel is diluted.
[0005] (3) Pyrometallurgical recycling: Waste is fed into a non-ferrous metal smelting furnace, allowing nickel / copper to enter the alloy phase, and nickel and copper are recovered. Barium titanate has a low recovery rate, and Ti in barium titanate is low at high temperatures. 4+ Easily reduced to Ti 3+ This generates oxygen vacancies, leading to increased dielectric loss and decreased insulation resistance.
[0006] (4) Hydrometallurgical recovery: Acid leaching is used to dissolve metals such as barium, titanium, nickel, copper, and silver in waste, and then extraction, precipitation and other methods are used to separate and recover nickel, barium, titanium, and silver. This method can achieve element-level recovery, but the process is long, acid and alkali consumption is large, wastewater treatment costs are high, electrode metal impurities are not completely removed, and the loss of barium and titanium components due to acid dissolution during acid leaching leads to a shift in stoichiometry. The residual nickel, copper, and silver in the regenerated powder is usually above 100 ppm, which cannot meet the purity requirements of MLCCs, has poor economic efficiency, and is difficult to apply on a large scale.
[0007] Therefore, most of the waste generated during MLCC production is currently disposed of through rigid landfill or co-processed in cement kilns, resulting in the near-complete loss of barium titanate and rare earth elements, which wastes resources and easily pollutes the environment. Summary of the Invention
[0008] The purpose of this application is to overcome the shortcomings of the prior art and to provide a method for preparing MLCC barium titanate ceramic powder using MLCC waste.
[0009] The method for preparing MLCC barium titanate ceramic powder using MLCC waste provided in this application includes the following steps: S1 recycles, crushes, and sieves the waste generated during the MLCC production process to remove magnetic metal debris and obtain ceramic powder. S2 The ceramic powder is prepared into a slurry, and the pH value is adjusted according to the electrode type of the waste before electrochemical treatment is carried out to remove nickel, copper and silver electrode metal impurities. S3 separates the solid and liquid components of the electrochemically treated slurry and dries it to obtain pretreated powder. S4. The pretreated powder is pre-calcined at a low temperature of 400-600°C for 1-3 hours to obtain pre-calcined powder; S5. The pre-calcined powder is dispersed in an aqueous phase to form a suspension. A dopant consisting of a mixture of yttrium oxide, manganese oxide, and silicon oxide is added to carry out a co-precipitation reaction, so that the dopant component is uniformly coated on the surface of the pre-calcined powder particles in the form of hydroxide. After aging, a coated precursor slurry is obtained. S6. Dry the coated precursor slurry to obtain a precursor powder with uniformly coated doped components on the surface. S7 The precursor powder is pre-calcined at a medium temperature of 800-1000°C for 1-2 hours to form a shell precursor; S8 The powder that has been pre-calcined at medium temperature is calcined at 1050-1200℃ for 2-4 hours to form a doped shell on the surface of barium titanate particles, while the particles retain a pure tetragonal barium titanate core, thus constructing a core-shell structure. S9 The core-shell structure is ground to D50=0.2~0.5μm, and then washed until the conductivity of the filtrate is <5μS / cm and the sulfate ion is <1ppm and the chloride ion is <0.5ppm; S10 The washed powder is formulated into a slurry, and a coupling agent is added for surface modification; S11 The modified slurry is dried and granulated, and after demagnetization treatment, barium titanate ceramic powder of MLCC is obtained.
[0010] In some embodiments of the method for preparing MLCC barium titanate ceramic powder using MLCC waste, in step S2, the pH value is adjusted according to the electrode type of the waste as follows: 2.2-2.8 for waste containing nickel electrodes, 2.5-3.0 for waste containing copper electrodes, 2.0-2.3 for waste containing silver electrodes, and 2.0-2.2 for waste of electrodeless pure ceramics.
[0011] In some embodiments of the method for preparing MLCC barium titanate ceramic powder using MLCC waste in this application, when the S4 step is carried out at low temperature, the temperature is raised from room temperature to 400-600°C at a rate of ≤2°C / min in an air atmosphere, held for 1-3 hours and then cooled with the furnace, so that the organic residual carbon content in the powder after low temperature pre-firing is <0.1wt%.
[0012] In some embodiments of the method for preparing MLCC barium titanate ceramic powder using MLCC waste in this application, in step S5, the dopant comprises the following raw materials in weight percentages: yttrium oxide 0.3%–0.6%, manganese oxide 0.1%–0.3%, and silicon dioxide 0.2%–0.4%; the amount of the dopant added is 0.6%–1.3% of the weight of the low-temperature pre-fired powder.
[0013] In some embodiments of the method for preparing MLCC barium titanate ceramic powder using MLCC waste, in step S5, during the coprecipitation reaction, the solution pH is adjusted to 9-11, the reaction temperature is 40-60℃, the stirring rate is 200-500 rpm, the aging time is 2-6 hours, the thickness of the doped layer on the surface of the coated particles is 5-15 nm, and the relative standard deviation of doping uniformity is <3%.
[0014] In some embodiments of the method for preparing MLCC barium titanate ceramic powder using MLCC waste in this application, when the S7 step is carried out at a medium temperature for pre-firing, the temperature is raised from room temperature to 800-1000°C at a rate of ≤2°C / min in an air atmosphere, held at that temperature for 1-2 hours, and then cooled with the furnace.
[0015] In some embodiments of the method for preparing MLCC barium titanate ceramic powder using MLCC waste, in step S8, high-temperature calcination is carried out in an air atmosphere with segmented temperature control: the first stage is to raise the temperature from room temperature to 600°C at a rate of ≤2°C / min and hold for 0.5 to 1 hour; the second stage is to raise the temperature from 600°C to 900°C at a rate of ≤1.5°C / min; the third stage is to raise the temperature from 900°C to a calcination temperature of 1050 to 1200°C at a rate of ≤1°C / min and hold for 2 to 4 hours; the fourth stage is to cool the temperature to below 300°C at a rate of ≤1°C / min; and the fifth stage is to cool the furnace to room temperature.
[0016] In some embodiments of the method for preparing MLCC barium titanate ceramic powder using MLCC waste in this application, in step S9, the grinding beads have particle sizes of 0.1 mm and 0.3 mm, are mixed at a mass ratio of 3:7, and the sand mill cylinder is water-cooled and the temperature is controlled at ≤35℃; the washing adopts a three-stage countercurrent washing process, and the washing endpoint simultaneously meets the dual index judgment of conductivity and ion chromatography.
[0017] In some embodiments of the method for preparing MLCC barium titanate ceramic powder using MLCC waste in this application, in step S10, the coupling agent is γ-glycidyl etheroxypropyltrimethoxysilane or γ-methacryloyloxypropyltrimethoxysilane, and the amount added is 0.5% to 1.5% of the weight of the washed powder; during modification, the pH of the slurry is adjusted to 4.0 to 5.0, the temperature is 40 to 60°C, and the mixture is stirred for 1 to 2 hours, then aged at a constant temperature for 2 to 4 hours, and then homogenized at high speed for 20 to 40 minutes.
[0018] This application also provides a multilayer ceramic capacitor, including a ceramic dielectric layer, wherein the ceramic dielectric layer is prepared using barium titanate ceramic powder material for MLCCs using the method described above.
[0019] The method for preparing MLCC barium titanate ceramic powder using MLCC waste provided in this application has the following beneficial effects: (1) This application incorporates a doping process between the low-temperature pre-calcination process for removing organic impurities and the high-temperature calcination process for reconstructing the crystal phase, thereby completing the liquid-phase chemical coating process. This allows the dopant to be uniformly coated on the surface at a molecular-level thickness in the intermediate state before the particles are densified. The diffusion depth is then precisely controlled by segmented temperature-controlled calcination. This process node selection overcomes the defects of "doping before calcination leading to titanium ion reduction" and "doping after calcination failing to form a shell".
[0020] (2) Deep removal of electrode metal impurities: Based on the electrode type of the waste, the pH conditions are optimized for different electrochemical characteristics of nickel, copper, silver and no electrode. The pH value is adjusted differently before electrochemical removal of heavy metals. Combined with precision filtration to intercept heavy metal colloids, the nickel removal rate is >99%, nickel <30ppm, copper <20ppm, silver <25ppm, which is far superior to the traditional acid washing process. This effectively improves the impurity removal rate and solves the problem of insufficient purity of regenerated powder.
[0021] (3) Low-temperature pre-calcination for independent impurity removal: The dried powder is pre-calcined at a low temperature of 400-600℃, which can completely remove residual organic binders and residual carbon, while avoiding the growth of barium titanate grains, keeping the particle surface clean and highly reactive, providing a good substrate for subsequent liquid phase chemical coating, and solving the problem of organic residue affecting the uniformity of doping.
[0022] (4) Liquid-phase chemical coprecipitation coating achieves molecular-level uniform doping. The coprecipitation method is used to uniformly deposit the dopant in the form of hydroxide on the surface of barium titanate particles. The coating thickness is 5-15 nm, and the doping uniformity RSD is <3%, which is far superior to the physical mixing method (RSD is usually >10%). This solves the problem of uneven dispersion of trace dopants and lays the foundation for the uniform construction of the core-shell structure.
[0023] (5) The dopant used for the regenerated powder is a mixture of yttrium oxide, manganese oxide and silicon oxide, which can suppress the reduction of titanium ions, improve the stability of dielectric constant, reduce dielectric loss, and improve the electrical performance and reliability of the regenerated barium titanate ceramic powder.
[0024] (6) The system employs a two-stage temperature-controlled in-situ construction of a core-shell structure using a combination of medium-temperature pre-calcination and high-temperature calcination. First, medium-temperature pre-calcination at 800–1000℃ decomposes the hydroxide coating into oxides, which then diffuse to form a shell precursor. Next, high-temperature calcination at 1050–1200℃ further diffuses the doped components into the particle interior by 10–30 nm, maintaining a pure tetragonal barium titanate core within the particle and forming a doped pseudo-cubic shell on the surface, thus constructing a stable core-shell structure in situ. This core-shell structure enables the powder to simultaneously possess high dielectric constant and excellent temperature stability, significantly improving high-temperature reliability.
[0025] (7) During the powder preparation stage, calcination was carried out in an air atmosphere, combined with segmented temperature control curves, which not only thoroughly removed organic matter but also effectively inhibited Ti. 4+ Restore to Ti 3+ Dielectric loss tanδ ≤ 1.5%, insulation resistance ≥ 10 Ω·cm 12 Ω, significantly improving dielectric properties.
[0026] (8) Dual endpoint washing judgment ensures reliability. The slurry after sand milling is washed until the conductivity of the filtrate is <5μS / cm and the sulfate ion is <1ppm and the chloride ion is <0.5ppm before modification treatment. This can eliminate the high temperature and high humidity insulation failure and electrode migration caused by chloride ions, and significantly improve the long-term reliability of the product.
[0027] The method for preparing MLCC barium titanate ceramic powder using MLCC waste provided in this application enables the recycled powder prepared from the waste during MLCC production and processing to form a stable core-shell structure, which can be used as a substrate for barium titanate ceramic materials, realizing the high-value resource utilization of industrial solid waste.
[0028] When the barium titanate ceramic powder for MLCCs prepared using the method described in this application is used as a material for the ceramic dielectric layer in multilayer ceramic capacitors, it exhibits good electrochemical performance. This provides a promising application prospect for the high-value recycling of waste materials from MLCC production and processing, resulting in significant economic and social benefits. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0030] This application first provides an embodiment of a method for preparing MLCC barium titanate ceramic powder using MLCC waste, comprising the following steps: S1 recycles, crushes, and sieves the waste generated during the MLCC production process to remove magnetic metal debris, thus obtaining ceramic powder.
[0031] In this step, waste materials from MLCC production and processing (such as chamfering mud, unqualified blanks, etc.) can be crushed by an air jet mill until they all pass through a 200-mesh sieve. The crushed material is then filtered by a first-stage 15,000-gauss electromagnetic separator to remove magnetic metal debris, and then stored in a sealed silo lined with polytetrafluoroethylene.
[0032] S2 involves preparing ceramic powder into a slurry, adjusting the pH value according to the electrode type of the waste, and then performing electrochemical treatment to remove nickel, copper, and silver electrode metal impurities.
[0033] In this step, the crushed, sieved, and demagnetized ceramic powder is prepared into a slurry with a solid content of 10% to 20%, placed in an electrochemical tank, and the pH value is adjusted according to the electrode type of the waste: the pH value of the waste slurry containing nickel electrodes is controlled between 2.2 and 2.8, the pH value of the waste slurry containing copper-terminal electrodes is controlled between 2.5 and 3.0, the pH value of the waste slurry containing silver electrodes is controlled between 2.0 and 2.3, and the pH value of the pure ceramic waste slurry without electrodes is controlled between 2.0 and 2.2.
[0034] During electrochemical treatment, graphite anodes and stainless steel cathodes are used, with an electrode spacing of 10–30 mm, a cell voltage of 3.0–4.5 V, a cathode current density of 30–40 A / m², and a hydraulic retention time of 30–60 minutes. The treatment method involves: under acidic conditions, electrode metal particles or ions such as nickel and copper migrate directionally to the cathode surface under the influence of an electric field, depositing and enriching themselves, thus achieving separation from the ceramic powder; a 0.1 μm precision filter is used to circulate the electrolyte and remove heavy metal colloids, preventing secondary adsorption and contamination. A hydrogen concentration alarm is installed above the electrochemical cell; the system automatically shuts down when the hydrogen concentration exceeds 0.4% by volume.
[0035] This step addresses the differences in electrochemical dissolution and deposition potentials of different electrode metals in the waste material by differentially optimizing pH conditions: nickel exhibits significantly improved dissolution efficiency at pH < 2.8, while copper shows optimal deposition selectivity within the pH range of 2.5–3.0 and silver within the pH range of 2.0–2.3, thus avoiding the problem of incomplete removal of metal impurities under uniform pH conditions. After electrochemical treatment, the nickel content in the slurry can be reduced from several thousand ppm initially to below 30 ppm, copper to below 20 ppm, and silver to below 25 ppm.
[0036] S3 separates the solid and liquid components of the electrochemically treated slurry. The filter cake is then acid-washed to remove impurities, washed until neutral, and dried to obtain pretreated powder.
[0037] In this step, the electrochemically treated slurry is settled in an inclined tube sedimentation tank for 1 to 2 hours, with the underflow concentration controlled at 15% to 20%. A 0.1 to 0.5 μm microfiltration device is installed at the end of the sedimentation tank to recover the ultrafine powder lost with the supernatant. A membrane filter cloth plate and frame filter is used for pressing, with a feed pressure of 0.6 to 0.8 MPa and a filter cake moisture content of 25% to 30%.
[0038] The filter cake is subjected to deep acid washing with dilute sulfuric acid or dilute hydrochloric acid at a concentration of 0.5–2.0 mol / L, a solid-liquid ratio of 1:5–1:10, a temperature of 40–60℃, and stirring for 1–2 hours to further remove residual metallic impurities such as nickel, copper, silver, and iron from the particles. After acid washing, the filter cake is washed with deionized water until the pH of the filtrate reaches 6.5–7.5.
[0039] Then, the wet filter cake is dried using the waste heat from the exhaust gas of a regenerative thermal oxidizer (RTO), with an indirect heat exchange mode to prevent direct contact between flue gas and powder. The drying temperature is 180–220℃, and the moisture content of the dried material is 3%–5%.
[0040] S4 The pretreated powder is pre-calcined in air at a low temperature of 400-600℃ for 1-3 hours to remove residual organic impurities and obtain pre-calcined powder.
[0041] This step involves low-temperature pre-firing in an air-atmosphere box furnace or roller kiln, raising the temperature from room temperature to 400–600°C at a rate of ≤2°C / min, holding the temperature for 1–3 hours, and then cooling it with the furnace.
[0042] The purpose of low-temperature pre-calcination is to thoroughly remove residual organic binders, dispersants, and carbon residues from the powder, while avoiding excessively high temperatures that could lead to abnormal growth of barium titanate grains. When the pre-calcination temperature is below 700℃, barium titanate grains do not grow significantly, and the particle surface maintains high reactivity, providing a clean substrate for subsequent liquid-phase chemical coating. After low-temperature pre-calcination, the organic carbon residue content in the powder is <0.1wt%.
[0043] This step uses an air atmosphere, not a reducing atmosphere, because there is no nickel internal electrode that needs protection during the powder preparation stage, and an air atmosphere can avoid the presence of Ti. 4+ Restore to Ti 3+ .
[0044] S5 disperses the pre-calcined powder in an aqueous phase to form a suspension, adds a dopant consisting of a mixture of yttrium oxide, manganese oxide, and silicon oxide, adjusts the pH value to 9-11 to carry out a co-precipitation reaction, so that the dopant components are uniformly coated on the surface of the pre-calcined powder particles in the form of hydroxides, and after aging, a coated precursor slurry is obtained.
[0045] In this step, the pre-calcined powder is first dispersed in deionized water with a solid content of 15%–25%. A dispersant (such as ammonium polyacrylate, added at 0.5–1.0 wt%) is added, and the mixture is stirred at high speed for 30–60 minutes to form a uniform suspension. Yttrium oxide (Y₂O₃, purity ≥99.99%), manganese oxide (MnO, purity ≥99.99%), and silicon oxide (SiO₂, purity ≥99.99%) are selected, with the following weight percentages: yttrium oxide 0.3%–0.6%, manganese oxide 0.1%–0.3%, and silicon dioxide 0.2%–0.4%. The amount of dopant added is 0.6%–1.3% of the weight of the pre-calcined powder.
[0046] The dopant is slowly added to the suspension while stirring. The pH is then adjusted to 9–11 with ammonia or sodium hydroxide solution. The mixture is reacted at 40–60°C and 200–500 rpm for 1–2 hours to allow the added dopant to co-precipitate uniformly on the surface of the barium titanate particles. The mixture is then aged for 2–6 hours to make the coating layer dense and uniform.
[0047] After co-precipitation coating, a uniform doped layer with a thickness of 5–15 nm is formed on the particle surface, with a relative standard deviation (RSD) of doping uniformity of <3%. Transmission electron microscopy shows that the doped layer is continuous, without agglomeration or local enrichment.
[0048] This step, adding dopants to the suspension, significantly improves the overall performance of the ceramic dielectric, reduces energy consumption, and enhances densification, thus contributing to improved product consistency and yield. Among the dopants mentioned above, yttrium oxide is a rare-earth acceptor dopant, which is activated by Yx... 3+Replacing Ti sites to capture oxygen vacancies suppresses titanium ion reduction, stabilizes the lattice structure of barium titanate powder, and improves insulation resistance, thereby reducing dielectric loss and improving the electrical performance and reliability of regenerated barium titanate ceramic powder. Manganese oxide, as a transition metal dopant, can regulate the Curie temperature and dielectric constant temperature characteristics, optimize dielectric properties, improve temperature stability, and enhance the long-term reliability of MLCCs in harsh environments such as high temperature and high humidity. Silica can act as a sintering aid, forming a liquid phase at grain boundaries to promote uniform grain growth, inhibit abnormal growth, improve grain bonding, and reduce grain boundary resistance, thus reducing dielectric loss, improving dielectric constant stability, and lowering losses.
[0049] S6 The coated precursor slurry is fed into a spray drying device for spray drying. The inlet temperature is 180–220℃, the outlet temperature is 80–100℃, and the atomizing disc speed is 10,000–15,000 rpm. After spray drying, spherical precursor particles with good flowability are obtained, with the particle surface uniformly coated with dopant components and a moisture content of <2%.
[0050] S7 The precursor powder is pre-calcined in air at a temperature of 800-1000℃ for 1-2 hours to decompose the hydroxide in the coating layer into oxides and diffuse them to the particle surface to form a shell precursor.
[0051] This step involves medium-temperature preheating in an air atmosphere box furnace, raising the temperature from room temperature to 800–1000°C at a rate of ≤2°C / min, holding at 800–1000°C for 1–2 hours, and then cooling it with the furnace.
[0052] The purpose of medium-temperature pre-calcination is: ① to decompose the hydroxides in the coating layer into the corresponding oxides; ② to allow the decomposed oxides to initially diffuse to the surface of barium titanate particles and react with the surface BaTiO3 in a solid-phase reaction to form a shell precursor; ③ to remove the trace amounts of moisture and organic dispersants remaining after spray drying.
[0053] This step controls the pre-calcination temperature at 800–1000℃. Within this temperature range, the doped oxide begins to diffuse but has not yet penetrated deep into the particle, thus avoiding excessive diffusion of the dopant and contamination of the core region. X-ray diffraction analysis shows that no pyrochlore phase (such as Ho2Ti2O7) second phase is formed after pre-calcination, indicating that the co-precipitation coating method effectively avoids the reaction of the dopant element with barium titanate to form impurity phases.
[0054] S8 calcines the pre-calcined powder at medium temperature in an air atmosphere at a temperature of 1050-1200℃ for 2-4 hours, allowing the dopant components to diffuse further into the particle interior, forming a doped shell layer with a thickness of 10-30nm on the surface of the barium titanate particles, while maintaining a pure tetragonal barium titanate core inside the particles, thus constructing a core-shell structure and obtaining the calcined material.
[0055] This step involves high-temperature calcination in an air-atmosphere roller kiln or box furnace. A segmented temperature control method is employed. First stage: Increase the temperature from room temperature to 600℃ at a rate of ≤2℃ / min and hold for 0.5 to 1 hour to remove any trace amounts of carbon and moisture that may remain after medium-temperature pre-calcination; The second stage involves increasing the temperature from 600℃ to 900℃ at a rate of ≤1.5℃ / min. During this stage, the doped oxide begins to diffuse into the interior of the particle. The third stage: the temperature is raised from 900℃ to 1050~1200℃ at a rate of ≤1℃ / min and held for 2~4 hours. During this stage, the doping component diffuses further into the particle interior by 10~30nm to form a stable doped shell. The particle interior maintains a pure tetragonal barium titanate core, and the core-shell structure is finalized. Fourth stage: Cool down to below 300℃ at a rate of ≤1℃ / min to eliminate internal residual stress; Fifth step: Cool to room temperature in the furnace and then remove from the furnace.
[0056] After high-temperature calcination, the barium titanate particles form a typical core-shell structure: the core region is pure tetragonal BaTiO3, maintaining a high ferroelectric phase and providing a high dielectric constant, c / a ≥ 1.008; the shell region has a thickness of 10–30 nm, providing temperature stability and DC bias stability. The grain size D50 is 150–250 nm, with uniform grain size distribution and no abnormally large grains.
[0057] This step uses an air atmosphere for calcination, which can effectively prevent Ti from being calcined. 4+ Restore to Ti 3+ This ensures the powder has high insulation resistance and low dielectric loss. After calcination, it can be slowly cooled in a high-purity alumina slow-cooling chamber, and then demagnetized at 15,000 gauss in two stages.
[0058] S9 The core-shell structured powder is ground to D50=0.2~0.5μm, and then washed until the conductivity of the filtrate is <5μS / cm and the sulfate ion is <1ppm and the chloride ion is <0.5ppm.
[0059] In this step, zirconium oxide grinding beads with a purity ≥99.9% and particle sizes of 0.1mm and 0.3mm are first mixed at a mass ratio of 3:7. Deionized water is added to the core-shell structure powder to make the slurry solid content 30%–40%. The grinding cylinder is water-cooled and the temperature is controlled at ≤35℃. Grinding is carried out until D50 = 0.2–0.5μm. An online laser particle size analyzer is installed at the discharge end. Unqualified particles are automatically returned for re-grinding. After grinding, the material can undergo a third-stage demagnetization at 15000 Gauss.
[0060] Then, deionized water with a resistivity ≥15 MΩ·cm was used for three-stage countercurrent washing, followed by pressure filtration dehydration after each stage of washing. The washing endpoint was determined by two criteria: the conductivity of the eluent was <5 μS / cm, and the sulfate ion concentration and chloride ion concentration detected by ion chromatography were <1 ppm and <0.5 ppm, respectively. The washing process was considered complete only if both criteria were met simultaneously.
[0061] S10 prepares the washed powder into a slurry and adds a silane coupling agent for surface modification.
[0062] In this step, the washed powder is first prepared into a slurry with a solid content of 25% to 30%, and then silane coupling agents γ-glycidoxypropyltrimethoxysilane (KH-560) or γ-methacryloyloxypropyltrimethoxysilane (KH-570) are added to improve the slurry dispersibility and uniformity. It can also improve the interfacial bonding performance between the prepared barium titanate powder and the metal electrode.
[0063] The amount of silane coupling agent added is 0.5% to 1.5% of the weight of the washed powder. During modification, the pH of the slurry is adjusted to 4.0 to 5.0, and the mixture is stirred at high speed for 1 to 2 hours at a temperature of 40 to 60°C.
[0064] After modification, the powder is aged at a constant temperature for 2–4 hours, followed by high-speed homogenization for 20–40 minutes to better disperse the powder and further improve interfacial bonding and durability. After aging, a fourth stage of 15,000 gauss demagnetization can be performed.
[0065] S11 dried and granulated the modified slurry, and after demagnetization, obtained MLCC barium titanate powder.
[0066] In this step, the modified slurry can be spray-dried and granulated with an inlet air temperature of 200-240℃ and an outlet air temperature of 90-110℃. The granulation D50 is 1.5-3.0μm. Then, after multi-stage electromagnetic demagnetization, the finished barium titanate powder is obtained.
[0067] The finished barium titanate powder prepared by the method described in this application has a laser particle size D50 of 0.2–0.5 μm and a D90 / D50 ≤ 1.5; XRD analysis shows it to be a pure tetragonal phase with c / a ≥ 1.008; TEM analysis shows it to have a core-shell structure with a shell thickness of 10–30 nm; ICP-MS analysis shows iron < 50 ppb, chromium < 20 ppb, nickel < 30 ppb, silver < 5 ppb, copper < 20 ppb, and lead < 10 ppb; dielectric loss tanδ ≤ 1.5% and insulation resistance IR ≥ 10¹² Ω.
[0068] In the method for preparing barium titanate ceramic powder for MLCCs using MLCC waste described in this application, a liquid-phase chemical coating process (S5-S6) is inserted between the low-temperature pre-firing (step S4) and the medium- and high-temperature calcination (steps S7-S8). This choice of process node is the core innovative feature of this application. If the dopant is added before the low-temperature pre-firing and then directly calcined at high temperature, the dopant will coexist with residual organic carbon, and the reduction of carbon at high temperature will lead to Ti… 4+ In traditional methods, the dopant rapidly and uniformly diffuses into the particle interior, failing to form a gradient shell. If high-temperature calcination is performed first to remove impurities before adding the dopant and then calcining again, the particles are already densified after the first high-temperature calcination, grain boundary migration stops, and the dopant can only accumulate at the grain boundaries, unable to diffuse directionally into the particle interior to form a shell. This application employs liquid-phase chemical coating after low-temperature pre-calcination (when the particle surface is clean, not yet densified, and maintains high reactivity). This allows the dopant to be uniformly deposited on the particle surface at a molecular-level thickness. Subsequent two-stage temperature-controlled calcination precisely regulates the diffusion depth, thus successfully constructing a gradient-distributed core-shell structure.
[0069] This application also provides a multilayer ceramic capacitor, including a ceramic dielectric layer, wherein the ceramic dielectric layer can be prepared using barium titanate ceramic powder for MLCCs as the dielectric material, thereby realizing the recycling and utilization of MLCC waste.
[0070] The method for preparing MLCC barium titanate ceramic powder using MLCC waste will be further described in detail below with reference to specific embodiments.
[0071] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.
[0072] Example 1 This embodiment 1 includes the following steps: S1 takes 100kg of grinding scrap (beveling putty) from nickel internal electrode MLCCs. The main components are: barium titanate about 65%, nickel electrode metal about 12%, glass phase about 5%, rare earth oxides about 3%, organic matter about 8%, and grinding media impurities about 7%.
[0073] The powder is crushed by a zirconia-lined airflow pulverizer until it passes through a 200-mesh sieve, and then demagnetized by a 15,000-gauss electromagnetic demagnetizer in the first stage. 1.2 kg of demagnetized slag is collected, and the powder is stored in a sealed PTFE-lined silo.
[0074] S2 prepares the powder into a slurry with a solid content of 15%, adjusts the pH to 2.5 with dilute sulfuric acid, and adds it to the electrochemical tank. The tank uses a graphite anode and a stainless steel cathode with a 20mm electrode spacing. The tank voltage is 3.8V, the cathode current density is 35A / m², and the hydraulic residence time is 45min. The electrolyte is circulated using a 0.1μm precision filter to remove heavy metal colloids. A hydrogen concentration alarm is installed above the electrochemical tank; the system automatically shuts down when the hydrogen concentration exceeds 0.4% by volume.
[0075] After treatment, the nickel content decreased from approximately 120,000 ppm to below 25 ppm, and the copper content decreased from approximately 500 ppm to below 15 ppm.
[0076] S3: The electrochemically treated slurry was settling in an inclined tube for 1.5 hours, with an underflow concentration of 18%. 1.5 kg of ultrafine powder was recovered via 0.5 μm microfiltration. The plate and frame filter press was used with a feed pressure of 0.7 MPa and a filter cake moisture content of 27%. The cake was then acid-washed with 1.0 mol / L dilute sulfuric acid at a solid-liquid ratio of 1:8 at 50°C and stirred for 1.5 hours. After acid washing, it was washed with deionized water until the pH reached 7.0. Finally, it was dried using a RTO with waste heat and hollow paddles at an inlet air temperature of 200°C. The dry material moisture content was 4.0%, yielding approximately 52 kg of pretreated powder.
[0077] S4: The pretreated powder is loaded into a corundum sagger, with a material layer of 3 cm, and pre-fired at a low temperature in an air atmosphere box furnace: the temperature is increased to 500℃ at a rate of 1.8℃ / min, held at 500℃ for 2 hours, and then cooled with the furnace. The residual carbon content of the pre-fired powder is 0.05wt%, yielding approximately 50 kg of pre-fired powder.
[0078] S5 disperses the pre-calcined powder in deionized water with a solid content of 20%, adds 0.8 wt% ammonium polyacrylate dispersant, and stirs at high speed for 45 minutes to form a suspension.
[0079] Prepare the doping solution: Y2O3 0.25kg (0.5%), MnO 0.1kg (0.2%), SiO2 0.15kg (0.3%), total 0.5kg (1.0%).
[0080] The dopant was slowly added to the suspension, the pH was adjusted to 10 with ammonia, the temperature was 50℃, the stirring speed was 300 rpm, the reaction was carried out for 1.5 h, and the mixture was aged for 4 h to obtain the coated precursor slurry. The thickness of the doped layer on the particle surface after coating was approximately 8 nm, and the RSD of Dy content was 2.0% at five sampling points.
[0081] S6 spray-dries the coated precursor slurry at an inlet temperature of 200℃, an outlet temperature of 90℃, and an atomizing disc rotation speed of 12000rpm, yielding approximately 51kg of precursor powder with a moisture content of 1.5%.
[0082] S7 loaded the precursor powder into a corundum sagger and pre-fired it at a medium temperature in an air atmosphere: the temperature was increased to 900℃ at a rate of 1.8℃ / min, held at 900℃ for 1.5 hours, and then cooled with the furnace. XRD analysis showed no pyrochlore phase second phase, yielding approximately 49 kg of the medium-temperature pre-fired material.
[0083] In S8, the pre-calcined material at medium temperature is loaded into a corundum sagger, with a material layer of 3 cm. It is then calcined at high temperature in an air-atmosphere roller kiln using a five-stage temperature control system: room temperature → 600℃, 1.8℃ / min, holding at 600℃ for 0.5 h; 600℃ → 900℃, 1.3℃ / min; 900℃ → 1150℃, 0.8℃ / min, holding at 1150℃ for 3 h; then cooled to 300℃ at a rate of 0.8℃ / min; followed by furnace cooling. The total cycle is approximately 24 hours. After slow cooling and secondary demagnetization, approximately 46 kg of core-shell structured calcined material is obtained.
[0084] XRD analysis: pure tetragonal phase, c / a=1.009; TEM analysis: clear core-shell structure, shell thickness approximately 18nm; SEM grain size D50=0.20μm.
[0085] S9 uses 0.1mm:0.3mm=3:7 zirconia beads to grind the core-shell structured calcined material, with a slurry solid content of 35%, water cooling at 32℃, and grinding to D50=0.30μm, D90 / D50=1.40, followed by third-stage demagnetization.
[0086] A three-stage countercurrent washing process was used with deionized water with a resistivity ≥15 MΩ·cm, followed by pressure filtration dewatering after each stage. Washing endpoint: conductivity 3.5 μS / cm, SO42- 2- =0.5ppm, Cl - =0.2ppm.
[0087] S10 prepares the washed powder into a slurry with a solid content of 25%, adds KH-560 for modification at a rate of 1.0% of the dry powder, sets the pH to 4.5, stirs at 50℃ for 1.5 hours, ages for 3 hours, homogenizes for 30 minutes, and then performs fourth-stage demagnetization.
[0088] S11 spray-dries the modified slurry with an inlet air temperature of 220°C and an outlet air temperature of 95°C, resulting in a granulation D50 of 2.0μm, followed by five-stage and six-stage demagnetization.
[0089] Finished product inspection: The finished product weighs approximately 42 kg, with an overall yield rate of 42%.
[0090] Test results: D50 = 0.30 μm, D90 / D50 = 1.40; c / a = 1.009; core-shell structure shell thickness 18 nm; Fe = 25 ppb, Cr = 10 ppb, Ni = 22 ppb, Cu = 12 ppb, Pb = 3 ppb; TOC = 50 ppm, moisture content 0.05%; dielectric loss tanδ = 1.0%, insulation resistance IR = 3 × 10⁻⁶12 Ω.
[0091] Example 2: This embodiment 2 includes the following steps: S1 contains 100kg of mixed scrap material from MLCCs with copper end electrodes. It contains approximately 8% copper and its main components are: approximately 62% barium titanate, approximately 8% copper electrode metal, approximately 6% glass phase, approximately 3% rare earth oxides, approximately 9% organic matter, and approximately 12% grinding media impurities.
[0092] The remaining steps are the same as in Example 1.
[0093] S2 prepares the powder into a slurry with a solid content of 15%, adjusts the pH to 2.8 with dilute sulfuric acid, and puts it into an electrochemical tank. The tank uses a graphite anode and a stainless steel cathode with a 20mm electrode spacing. The tank voltage is 4.0V, the cathode current density is 38A / m², and the hydraulic residence time is 45min. The electrolyte is circulated using a 0.1μm precision filter to remove heavy metal colloids. A hydrogen concentration alarm is installed above the electrochemical tank; the system automatically shuts down when the hydrogen concentration exceeds 0.4% by volume.
[0094] After treatment, the copper concentration decreased from approximately 80,000 ppm to below 18 ppm.
[0095] Steps S3-S7 are the same as in Example 1.
[0096] In step S8, the pre-calcined material at medium temperature is loaded into a corundum sagger, with a material layer of 3 cm. It is then calcined at high temperature in an air-atmosphere roller kiln using a five-stage temperature control system: room temperature → 600℃, 1.8℃ / min, holding at 600℃ for 0.5 h; 600℃ → 900℃, 1.3℃ / min; 900℃ → 1180℃, 0.8℃ / min, holding at 1180℃ for 2.5 h; then cooled to 300℃ at a rate of 0.8℃ / min; followed by furnace cooling. The total cycle is approximately 24 hours. After slow cooling, a second-stage demagnetization process yields approximately 46 kg of core-shell structured calcined material. The remaining processes are the same as in Example 1.
[0097] Finished product inspection: The finished product weighs approximately 40 kg, with an overall yield of 40%.
[0098] Test results: D50 = 0.28 μm, D90 / D50 = 1.38; c / a = 1.009; pure tetragonal phase, clear core-shell structure, shell thickness 22 nm; Fe = 22 ppb, Ni = 18 ppb, Cu = 15 ppb; tanδ = 0.9%, insulation resistance IR = 4 × 10⁻⁶ 12 Ω.
[0099] Example 3: This embodiment 3 includes the following steps: S1 takes 100kg of unqualified pure ceramic blank waste without electrodes. The main components are: barium titanate about 88%, glass phase about 5%, rare earth oxides about 4%, and organic matter about 3%.
[0100] The remaining steps are the same as in Example 1.
[0101] S2 prepares the powder into a slurry with a solid content of 15%, adds dilute sulfuric acid to adjust the pH to 2.1, and puts it into an electrochemical tank with graphite anode, stainless steel cathode, electrode spacing of 20mm, tank voltage of 3.2V, cathode current density of 30A / m², and hydraulic residence time of 45min.
[0102] This step primarily removes trace amounts of iron impurities introduced from the raw materials.
[0103] The remaining processes are the same as in Example 1.
[0104] Finished product inspection: Approximately 75kg of finished product, with an overall yield rate of 75%.
[0105] Test results: D50 = 0.32 μm, D90 / D50 = 1.35; c / a = 1.010; pure tetragonal phase, clear core-shell structure, shell thickness 16 nm; Fe = 12 ppb, Ni = 3 ppb, Cu = 2 ppb; tanδ = 0.7%, insulation resistance IR = 8 × 10⁻⁶ 12 Ω has a purity superior to recycled products containing electrode waste.
[0106] Comparative Example 1: The raw materials and processes for Comparative Example 1 are the same as those for Example 1, except that: The S4 low-temperature pre-calcination process and the S5 liquid-phase chemical coating process are cancelled. The dopant was calcined at high temperature in step S8 and then mixed for 20 minutes. The S8 step of high-temperature calcination uses a low-oxygen, weak-reducing atmosphere (nitrogen carrier gas + 0.3% CO, oxygen content 0.3%), and non-segmented temperature control, directly raising the temperature to 1150℃ and holding it for 2.5 hours.
[0107] Finished product inspection: TEM analysis showed no obvious core-shell structure, and dopant elements were enriched at grain boundaries; XRD analysis revealed the presence of Ti. 3+ Characteristic peaks of the reduced phase; Y content RSD = 13.5% (five-point sampling); tanδ = 3.2%; insulation resistance IR = 2 × 10⁻⁶. 10 Ω, which is two orders of magnitude lower than that of Example 1.
[0108] This comparative example 1 illustrates that low-temperature pre-calcination for impurity removal, liquid-phase chemical coating doping, and two-stage temperature-controlled calcination in air atmosphere are crucial for constructing the core-shell structure and suppressing the valence change of titanium ions. Direct doping after calcination and a low-oxygen, weak-reducing atmosphere cannot obtain regenerated powder that meets the requirements of high-end MLCCs.
[0109] Comparative Example 2: The raw materials and processes for Comparative Example 2 are the same as those for Example 1, except that: In step S5, the dopant is directly mixed using a physical mixing method (the pre-calcined powder and barium titanate powder are mixed in a mixer for 30 minutes), without liquid-phase co-precipitation coating, thus eliminating step S6.
[0110] The remaining processes are the same as in Example 1.
[0111] Finished product inspection: Dy content RSD = 11.8% when sampled at five points; TEM inspection showed uneven shell thickness, some particles had no obvious shell, and some blanks showed abnormal grain growth.
[0112] Comparative Example 2 illustrates that the liquid-phase chemical coprecipitation coating method can more uniformly disperse trace dopants on the surface of barium titanate particles, thereby ensuring the uniform construction of the core-shell structure and product consistency. Physical mixing methods cannot achieve the same effect.
[0113] Comparative Example 3: The raw materials and processes for Comparative Example 3 are the same as those for Example 1, except that: In step S9, washing ends only when the conductivity is <5 μS / cm, and ion chromatography detection is not performed. Washing is stopped when the conductivity reaches the target.
[0114] Test result: SO4 2- =3.2ppm, Cl - =1.8ppm.
[0115] After the finished MLCCs were subjected to a high temperature and high humidity test at 85℃ / 85%RH for 500 hours, the insulation resistance IR decreased by two orders of magnitude, and traces of electrode migration caused by chloride ions appeared.
[0116] This comparative example 3 illustrates that the use of dual indicators to determine the washing endpoint in step S9 can ensure the long-term reliability of high-end products.
[0117] The above embodiments shown in this application are only part of the preferred embodiments of this application and should not be construed as limiting this application. Any modifications, equivalent substitutions and improvements made by those skilled in the art without departing from the spirit of this application shall be within the protection scope of this application.
Claims
1. A method for preparing MLCC barium titanate ceramic powder using MLCC waste, characterized in that, Includes the following steps: S1 recycles, crushes, and sieves the waste generated during the MLCC production process to remove magnetic metal debris and obtain ceramic powder. S2 The ceramic powder is prepared into a slurry, and the pH value is adjusted according to the electrode type of the waste before electrochemical treatment is carried out to remove nickel, copper and silver electrode metal impurities. S3 separates the solid and liquid components of the electrochemically treated slurry and dries it to obtain pretreated powder. S4. The pretreated powder is pre-calcined at a low temperature of 400-600°C for 1-3 hours to obtain pre-calcined powder; S5. The pre-calcined powder is dispersed in an aqueous phase to form a suspension. A dopant consisting of a mixture of yttrium oxide, manganese oxide, and silicon oxide is added to carry out a co-precipitation reaction, so that the dopant component is uniformly coated on the surface of the pre-calcined powder particles in the form of hydroxide. After aging, a coated precursor slurry is obtained. S6. Dry the coated precursor slurry to obtain a precursor powder with uniformly coated doped components on the surface. S7 The precursor powder is pre-calcined at a medium temperature of 800-1000°C for 1-2 hours to form a shell precursor; S8 The powder that has been pre-calcined at medium temperature is calcined at 1050-1200℃ for 2-4 hours to form a doped shell on the surface of barium titanate particles, while the particles retain a pure tetragonal barium titanate core, thus constructing a core-shell structure. S9 The core-shell structure is ground to D50=0.2~0.5μm, and then washed until the conductivity of the filtrate is <5μS / cm and the sulfate ion is <1ppm and the chloride ion is <0.5ppm; S10 The washed powder is formulated into a slurry, and a coupling agent is added for surface modification; S11 The modified slurry is dried and granulated, and after demagnetization treatment, barium titanate ceramic powder of MLCC is obtained.
2. The method for preparing MLCC barium titanate ceramic powder using MLCC waste as described in claim 1, characterized in that, In step S2, the pH value is adjusted according to the electrode type of the waste as follows: 2.2-2.8 for waste containing nickel electrodes, 2.5-3.0 for waste containing copper electrodes, 2.0-2.3 for waste containing silver electrodes, and 2.0-2.2 for waste containing electrodeless pure ceramics.
3. The method for preparing MLCC barium titanate ceramic powder using MLCC waste as described in claim 1, characterized in that, When the S4 step is low-temperature pre-firing, the temperature is raised from room temperature to 400-600°C at a rate of ≤2°C / min in an air atmosphere, held for 1-3 hours, and then cooled with the furnace to ensure that the organic residual carbon content in the powder after low-temperature pre-firing is <0.1wt%.
4. The method for preparing MLCC barium titanate ceramic powder using MLCC waste as described in claim 1, characterized in that, In step S5, the dopant comprises the following raw materials by weight percentage: Yttrium oxide 0.3%–0.6%, manganese oxide 0.1%–0.3%, silicon dioxide 0.2%–0.4%; The amount of dopant added is 0.6% to 1.3% of the weight of the low-temperature pre-fired powder.
5. The method for preparing MLCC barium titanate ceramic powder using MLCC waste as described in claim 1 or 4, characterized in that, In step S5, during the coprecipitation reaction, the solution pH is adjusted to 9-11, the reaction temperature is 40-60℃, the stirring rate is 200-500 rpm, the aging time is 2-6 hours, the thickness of the doped layer on the surface of the coated particles is 5-15 nm, and the relative standard deviation of doping uniformity is <3%.
6. The method for preparing MLCC barium titanate ceramic powder using MLCC waste as described in claim 1, characterized in that, When the S7 step is preheated at a medium temperature, the temperature is raised from room temperature to 800-1000°C at a rate of ≤2°C / min in an air atmosphere, held for 1-2 hours, and then cooled with the furnace.
7. The method for preparing MLCC barium titanate ceramic powder using MLCC waste as described in claim 1, characterized in that, In step S8, high-temperature calcination is carried out in an air atmosphere with segmented temperature control: the first segment raises the temperature from room temperature to 600℃ at a rate of ≤2℃ / min and holds it for 0.5 to 1 hour; the second segment raises the temperature from 600℃ to 900℃ at a rate of ≤1.5℃ / min; the third segment raises the temperature from 900℃ to 1050 to 1200℃ at a rate of ≤1℃ / min and holds it for 2 to 4 hours; the fourth segment cools the temperature to below 300℃ at a rate of ≤1℃ / min; and the fifth segment cools the furnace to room temperature.
8. The method for preparing MLCC barium titanate ceramic powder using MLCC waste as described in claim 1, characterized in that, In step S9, the grinding beads have particle sizes of 0.1 mm and 0.3 mm, and are mixed at a mass ratio of 3:
7. The sand mill cylinder is water-cooled and the temperature is controlled at ≤35℃. The washing adopts a three-stage countercurrent washing process, and the washing endpoint simultaneously meets the dual indicators of conductivity and ion chromatography.
9. The method for preparing MLCC barium titanate ceramic powder using MLCC waste as described in claim 1, characterized in that, In step S10, the coupling agent is γ-glycidyl etheroxypropyltrimethoxysilane or γ-methacryloyloxypropyltrimethoxysilane, and the amount added is 0.5% to 1.5% of the weight of the washed powder. During modification, the pH of the slurry is adjusted to 4.0 to 5.0, the temperature is 40 to 60°C, and the mixture is stirred for 1 to 2 hours. Then, it is aged at a constant temperature for 2 to 4 hours, and after aging, it is homogenized at high speed for 20 to 40 minutes.
10. A multilayer ceramic capacitor, characterized in that, Includes a ceramic dielectric layer, wherein the ceramic dielectric layer is prepared using the barium titanate ceramic powder material for MLCCs according to any one of claims 1-9.